2017
DOI: 10.1038/s41562-017-0054
|View full text |Cite
|
Sign up to set email alerts
|

Physically interacting individuals estimate the partner’s goal to enhance their movements

Abstract: From a parent helping to guide their child during their first steps, to a therapist 15 supporting a patient, physical assistance enabled by haptic interaction is a fundamental modus 16 for improving motor abilities. However, what movement information is exchanged between 17 partners during haptic interaction, and how this information is used to coordinate and assist 18 others remains unclear 1 . Here, we propose a model where haptic information, provided by touch 19 and proprioception 2 , enables int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
203
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(228 citation statements)
references
References 27 publications
21
203
4
Order By: Relevance
“…On the other hand, the study of physical tasks between humans has revealed how the capability to understand the partner's sensorimotor control and to adapt one's own control is key to interaction benefits [16]. Some recent papers have studied how finite games can deal with limited knowledge of the partner [17,18], but it is unclear how the available techniques should be transferred to the continuous control of the interaction with a robot.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the study of physical tasks between humans has revealed how the capability to understand the partner's sensorimotor control and to adapt one's own control is key to interaction benefits [16]. Some recent papers have studied how finite games can deal with limited knowledge of the partner [17,18], but it is unclear how the available techniques should be transferred to the continuous control of the interaction with a robot.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid emergence of stable coordination in rigid 445 coupling may be due to the fact that the partner actions are easier to predict and a 446 joint coordination strategy is simple to develop as the two subjects shared the same 447 task. However, dyads need more time to develop an interaction strategy when the task 448 is more challenging [4,10] or -as in the present study -when the subjects have different 449 and partly conflicting goals.…”
mentioning
confidence: 73%
“…For over a decade, sub-optimal and risk-seeking behaviours have been repeatedly confirmed in studies of motor decision-making tasks with an asymmetric gain function 4,5,6,8 , that require a choice with different variances of pay-off 2,3,7,9 and involve a speed-accuracy trade-off 10 we assessed the potential effect of interaction with opponents on sub-optimal motor decision-making with a prediction that other people's actions/intentions can influence the subjects' motor system 10,11,20,21 . First, we found that the subjects' risk-seeking strategy in the individual task reversed to risk-averse strategy at the very beginning of the competitive task ( Fig.…”
Section: Discussionmentioning
confidence: 96%